2015
DOI: 10.1080/10548408.2014.986018
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Outbound Tourism: an Epilogue

Abstract: As an epilogue to this special issue, this paper offers a brief critical review of Chineseoutbound-tourism literature, developed so far in conjunction with the articles accepted in this special issue. In doing so, we provide an overview of the state-of-the-art knowledge with regard to Chinese outbound tourism. Issues other than those presented in the special issue articles are also discussed and highlighted. These include the social and environment issues that could possibly prove not as positive as economic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 31 publications
(30 reference statements)
0
13
0
1
Order By: Relevance
“…Reviewing the past research on Chinese outbound tourism, Huang, Keating, Kriz, and Heung (2015) observed that research topics in this area evolved from market analysis to behavioral studies, and in the behavioral studies, the focus has shifted from travel motivations to home society cultural value and social facets explanations (Hsu & Huang, 2016). So far, most studies seeking understanding of Chinese outbound tourist behaviors have unanimously taken a consumer research perspective that looks into psychological constructs (e.g., motivation, attitude, and revisit intention) at individual levels; seldom have the social and economic structural factors been considered in explaining Chinese outbound travel behaviors at the society level.…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the past research on Chinese outbound tourism, Huang, Keating, Kriz, and Heung (2015) observed that research topics in this area evolved from market analysis to behavioral studies, and in the behavioral studies, the focus has shifted from travel motivations to home society cultural value and social facets explanations (Hsu & Huang, 2016). So far, most studies seeking understanding of Chinese outbound tourist behaviors have unanimously taken a consumer research perspective that looks into psychological constructs (e.g., motivation, attitude, and revisit intention) at individual levels; seldom have the social and economic structural factors been considered in explaining Chinese outbound travel behaviors at the society level.…”
Section: Introductionmentioning
confidence: 99%
“…收稿日期: 2018- 10-18 修订日期: 2018-11-27 基金项目: 国家自然科学基金项目(41801059); 国家 "万人计划" 青年拔尖人才支持计划项目; 国家社科基金重点项目(17AJY22)。 作者简介: 温晓金, 女, 山东莱芜人, 博士, 主要从事出入境旅游等研究。E-mail: wenxiaojin2008@163.com 通讯作者: 刘焱序, E-mail: yanxuliu@bnu.edu.cn 献。中国国家经济的繁荣、 中产阶级的崛起、 个人 和家庭可支配收入的增加是推动中国出境旅游快 速发展的关键因素 [5] 。不断开放的出境旅游政策和 日益成熟的互联网技术为中国公民个人出境旅游 提供了便利 [6] , 国际旅游成本的相对降低则进一步 增强了出境旅游的经济动机 [7] , 中国庞大的城市人 口基数和相对稳定的经济形势保障了充分的出境 旅游市场规模需求 [8] 。此外, 中国年轻出境群体追求 新奇乐于探索的价值观 [9] 、 老年出境群体较充裕的时 间和丰富人文情怀 [10] , 都决定了中国出境旅游市场 仍有较大的增长潜力。 当前, 中国出境旅游正经历着从 "数量驱动型" 到 "质量导向型" 的转变 [5] 。通过相关政府管理部门 对旅游企业、 大众传媒的正确引导, 以及对目的地 旅游市场的进一步开拓, 可有效地降低中国公民出 境的盲目性, 从而一方面增强中国公民对出境旅游 服务质量的满意度 [11] , 另一方面通过规范化的出境 旅游组织管理传播正面的中国国家形象 [12] 。然而, 近年来宏观统计层面对中国出境旅游的定量研究 仍以国家尺度的时序统计为主 [13] , 虽然少量涉及对 时空面板数据的归因 [14] , 但总体上对出境旅游空间 格局特征的凝练相对薄弱, 未能对中国旅游产业国 际化布局形成定量支撑。在中国出境旅游研究中, 对目的地国家旅游的产业发展水平、 目的地国家的 境外客源市场、 当地居民生活与国际旅游的关系等 议题的研究都有待进一步深化 [15] [16] 。新加坡作为知名旅游国, 接 待印尼、 中国、 印度、 澳大利亚、 日本、 马来西亚等国 游客规模相对多, 且增长趋势相对稳定 [17] 。而对于 邻近的印度而言, 美国和英国游客高居入境游客规 模的前两位, 中国游客则在十位以外 [18] 。作为穆斯 林国家的阿联酋以迪拜旅游为增长极, 大力发展航 空产业, 完善基础设施, 使阿联酋成为连通欧亚非 的新兴世界级旅游目的地 [19] 。伊朗的文化遗产也具 有宗教旅游吸引力, 但由于政治局势等因素的影 响, 其入境游客规模远小于同为穆斯林国家的土耳 其和埃及 [20] 。作为欧美游客传统旅游目的地的希 腊, 近年来受到中国游客的关注, 为东亚-东欧文 化交流提供了重要的连结纽带 [21] 。可见, 中国出境 游客在不同目的地国家旅游产业中的被重视程度 不一, 并且其地位受到中国出境旅游政策和目的地 国家入境旅游政策的共同影响。 2.3 地理空间分析方法对出入境旅游的刻画优势 地理学对出入境旅游研究的突出贡献表现为对 旅游规模空间结构及其演化规律的细致解析 [22,23] 。 李创新等 [24] 基于改进的熵值法, 刻画了 1993-2008 年中国大陆 31 个省市区的区域入境旅游流优势度, 为中国入境旅游流空间梯级网络结构分析提供了 技术支持。王凯等 [25] 利用标准差、 锡尔系数等计量 方法探讨了 1991-2010 年中国入境旅游发展时空差 异的动态演进过程, 发现中国区域入境旅游经济发 展总体上呈现出典型的非极化不平衡发展态势。薛 华菊等 [26] 采用空间自相关、 收入规模比例等方法对 中国入境旅游流质的研究发现, 中国东部地区主要 为规模-质量高耦合发展模式, 中部、 西部大部分 处于低耦合发展态势。刘军胜等 [27] [28][29][30][31] [36,37] [J]. Tourism Tribune, 2016, 31 (10): 45-55.…”
Section: 民心相通的发展愿景下, 为引导出境旅游布局提供unclassified
“…With its rise onto the world stage, China outbound tourism has received increasing scholarly attention. The growing literature has recently been reviewed by various researchers (Andreu, Claver, & Quer, ; Cai et al, ; Huang & Hsu, , ; Huang, Keating, Kriz, & Heung, ; Jin & Wang, ; Jørgensen, Law, & King, ; Keating, Huang, Kriz, & Heung, ; Keating & Kriz, ; Leung, Li, Fong, Law, & Lo, ; Tsang & Hsu, ; Tse, ). As observed by Jørgensen et al (), these reviews illustrate that the existing research on China outbound tourism has been limited in breadth and depth.…”
Section: The Scholarly Stereotypes Of Chinese Touristsmentioning
confidence: 99%